ВЕРХНІЙ ТИТОН ТЕТИЧНОЇ ПРОВІНЦІЇ: ЗОНАЛЬНІСЬ ТА КОРЕЛЯЦІЯ ЗА ТИНТИНІДАМИ - Zhabina, N.M. (Institute of Geological Sciences of the Ukrainian National Academy of Sciences, 2016)
Criterions for the zonation by tintinnids of the Upper Tithonian deposits in the sections of France, Austria, Slovak, Poland, Ukraine, Bulgaria, Rumania, Cuba, Italy, Georgia are given. In the regions of the Mediterranean belt zone Chitinoidella (subsones Dobeni and Boneti), Praetintinnopsella and Crassicollaria are distinguished, and characteristics of these zones are given by the analysis of the literary sources. By the correlation with the magnitostratigraphy and modern geologic scale subzone Dobeni is corresponding with transitional layers of Lower and Upper Tithonian (ammonites zones Ponti and Microcantum), subzone Boneti with the lower part of Upper Tithonian (lower part of Microcantum), zone Praetintinnopsella with the lower layers of Upper Tithonian, zone Crassicollaria with the interval of the ammonites zones – upper part of Micracanthoceras microcanthum, Durandites and lover part of Berriasella Jacobi. In majority of the regions only zone Crassicollaria is distinguished, but the criterions for its subdivision are different. The essential basis for determining of the lover boundary of zone is the sharp decreasing of the number of chitinoidellids and increasing of the variety and number of calpionellids. Crassicollaria, Tintinnopsella carpathica and Calpionella alpinа are dominating. In the upper boundary chitinoidellids decreased and the number of small Calpionella alpinа very increased in Lower Berriassian. Zones Chitinoidella (subzones Dobeni, Boneti) and Crassicollaria (Remanei, Intermedia) are determined in the Upper Tithonian deposits in Ukrainian Carpathian Foredeep. The changing of zonal associations happened gradually. In more yang subdivisions are present more antique elements. Characteristic specias of the Chitinoidella zone almost disappeared to the end of Remanei subzone. Tintinnopsella carpathica, T. remanei, various Crassicollaria and mostly small Calpionella alpinа are peculiar to this one. In subzone Intermedia the abundant of calpionellids and the number of big roundish C. alpinа increased, and the typical Berriassian specias appeared. Zonal taxons of calpionellids pass on the more yang zone Calpionella, in the lower border of which took place the C. alpinа bloom. Detailed characteristic of the Crassicollaria zone strong section in Ukraine is given.